O que vem depois das águas: entre arquivos da exceção e libertação da terra no Submédio São Francisco - Bezerra, Sabrina Maria Gonçalves Luz Barros (Universidade Federal de São Carlos, 2025)
This dissertation is the result of research conducted among archives that were opened due to the same problem: the conditions and effects of the appreciation of Caatinga lands and their relationship with water in the Submédio São Francisco Valley (SMFS). The investigation led me to the documents of three entities, in this order: i) the Superintendence for the Development of the Northeast (Sudene); ii) the Dom José Rodrigues Collection, the former library of the Diocese of Juazeiro-BA, designed by Bishop Dom José Rodrigues (1975-2003); and iii) the Archive of the Pastoral Land Commission of Juazeiro (CPT). Understood as distinct forms of constitution and visibility of formulations, the documentary and archival heterogeneity present here reflects forces that emerged and acted to transform or resist the changes imposed by development projects in the Submédio. Thus, a documentary fabric was constructed capable of deepening the relationship between the Public Irrigation Policies of the 1980s and the construction of the Sobradinho Dam in Bahia during the 1970s — whether through planning statements or through discourses of reaction and resistance. This documentary fabric constitutes the very essence of this research. That is, a documentation constructed under a relationship of forces. On the one hand, Sudene represents efforts to transform the São Francisco caatinga into an example of modernity and development, seeking to transform the exception of development into the rule; on the other, the CPT and the Diocese of Juazeiro bring together efforts aimed at the liberation of human beings and their lands. Thus, these archives can be understood, respectively, as archives of exception and archives of liberation — theoretical-methodological strategies that allow us to examine authors, testimonies, gaps and other elements, some of which have been eclipsed, related to the problem of water and land in the São Francisco.
What comes after the waters: between archives of exception and liberation of land in the Submédio São Francisco
Keywords: Arquivo; Diocese de Juazeiro; Comissão Pastoral da Terra; Sudene; Irrigação; Archive; Diocese of Juazeiro; Pastoral Land Commission; Sudene; Irrigation; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA RURAL